2014
DOI: 10.1007/s12035-014-8850-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The Clinical Utility of Matrix Metalloproteinase 9 in Evaluating Pathological Grade and Prognosis of Glioma Patients: A Meta-Analysis

Abstract: In the recent years, matrix metalloproteinase 9 (MMP-9) has been focused on as an indicator of glioma grade and prognosis, especially in China. However, all results resulted in many conflicts. So, it is necessary to conduct a meta-analysis to secure a convincing correlation between MMP-9 and grade and prognosis. Eligible studies were included via multiple searches, and then odds ratios (ORs) and hazard ratios (HRs) with 95% confidence intervals (95% CIs) were estimated. Funnel plots were available for evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Yang et al . () performed a meta‐analysis of studies on MMP‐9 in glioma and concluded that MMP‐9 is highly associated with high‐grade glioma and a poor 5‐year prognosis and that MMP‐9 testing in glioma tissues should be a routine clinical protocol in pathology departments.…”
Section: Pathologies: Predisposition Diagnosis and Therapy (Animal mentioning
confidence: 99%
“…Yang et al . () performed a meta‐analysis of studies on MMP‐9 in glioma and concluded that MMP‐9 is highly associated with high‐grade glioma and a poor 5‐year prognosis and that MMP‐9 testing in glioma tissues should be a routine clinical protocol in pathology departments.…”
Section: Pathologies: Predisposition Diagnosis and Therapy (Animal mentioning
confidence: 99%
“…PCNA, the expression of which is elevated in proliferating cells and in most malignant tumor cells, is commonly used as a proliferative/malignancy biomarker in cancer [25]. In addition, expression of MMP-9, which is associated with cell migration and extracellular matrix degradation, reflects the migration and invasion of tumor cells [26]. Our data suggest that SDC1 knockdown inhibits the proliferation and invasion of A172 and U87 cells by inhibiting PCNA and MMP-9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Gliomas have been reported as the most common one of primary cerebral tumors in central neural system. According to the regulation of World Health Organization (WHO) classification stantard, all gliomas can be divided into 4 grades on the basis of their histology [1][2]. Although some latest therapy technologies (resection and radio-/chemotherapy) have been introduced into the treatment of gliomas, the whole effects on patients with gliomas remain to be not satisfactory [3][4].…”
Section: Introductionmentioning
confidence: 99%